On a class of abstract degenerate multi-term fractional differential equations in locally convex spaces - Fedorov, Vladimir; Kostić, Marko (Eurasian Mathematical Journal, 2018)
In this paper, we consider regularized solutions for a class of abstract degenerate multi-term fractional differential equations with Caputo derivatives. Our results seem to be new even for non-degenerate differential equations under consideration.